Мікроконцептосфера «кохання» в сучасному жіночому романі (на матеріалі творів Дари Корній) - Макарова, Марина; Makarova, Maryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті запропоновано модель концептосфери КОХАННЯ, елементарним складником якої є концепт; описано мікроконцептосферу «кохання» в сучасному жіночому романі на матеріалі творів Дари Корній; проаналізовано засоби образності, що репрезентують індивідуально-авторський стиль письменниці.The model of kontceptosphere «love» as a collection of individual copyright of knowledge about this feeling (mikrokontseptosphere), the unit which is an integral part of the concept is considered in the article; mikrokontsetosphere «love» in the contemporary women's novel, on the materials of Dara Korney is described; the means of imagery that represent individual style of the writer are analyzed. In the article was made the emphasis on the metaphors, epithets, comparisons, graduations, personalization, etc. The article noted that the conceptual picture of the world is realized in the speech of an individual's view of the world through language. The use of certain language constructs allow a person to highlight the characteristics of the nation. Significantly affect on the formation of the picture of the world it is gender identity. Gender differentiation of society is realized in a specific men's and women's communicative activity that allows you to talk about the features reflect the linguistic world women writers. Individual-author picture of the world is a kind of interpretation of the individual perception of the world.
Mikrokontseptosphere «Love» in the Contemporary Women's Novel (Based on the Materials of Dara Korney)
Keywords: концептосфера; мікроконцептосфера; мікроконцепто- сфера «кохання»; концепт; жіночий роман; conceptosphere; mikrokontsetosphere; mikrokontsetosphere «love»; concept; women’s novel